A two-fold engineering approach based on Bi2Te3 flakes towards efficient and stable inverted perovskite solar cells. Issue 3 (26th May 2020) - Tsikritzis, Dimitris; Rogdakis, Konstantinos; Chatzimanolis, Konstantinos; Petrović, Miloš; Tzoganakis, Nikos; Najafi, Leyla; Martín-García, Beatriz; Oropesa-Nuñez, Reinier; Bellani, Sebastiano; Del Rio Castillo, Antonio Esaù; Prato, Mirko; Stylianakis, Minas M.; et al.
Abstract : An engineering approach is implemented for the performance and stability enhancement of perovskite solar cells, through the incorporation of bismuth telluride flakes in the electron transport layer (ETL) and as an interlayer on top of the ETL. Abstract : Perovskite solar cells (PSCs) are currently the leading thin-film photovoltaic technology owing to their high power conversion efficiency (PCE), as well as their low-cost and facile manufacturing process. Two-dimensional (2D) materials have been reported to improve both the PCE and the stability of PSCs when incorporated across the device's layered configuration. Hereby, a two-fold engineering approach is implemented in inverted PSCs by using ultra-thin Bi2 Te3 flakes, i.e. : (1) to dope the electron transport layer (ETL) and (2) to form a protective interlayer above the ETL. Thorough steady-state and time-resolved transport analyses reveal that our first engineering approach improves the electron extraction rate and thus the overall PCE (+6.6% vs. reference cells), as a result of the favourable energy level alignment between the perovskite, the ETL and the cathode. Moreover, the Bi2 Te3 interlayer, through the second engineering approach, facilitates further the electron transport and in addition protects the underlying structure against chemical instability effects, leading to enhanced device performance and stability. By combining the two engineering approaches, our optimised PSCs reach a PCE up to 19.46% (+15.2% vs. reference cells) and retain more than 80% of their initial PCE, after the burn-in phase, over 1100 h under continous 1 sun illumination. These performances are among the highest reported in the literature for inverted PSCs.